Pemanfaatan Teknologi Informasi dan Komunikasi sebagai Media Pembelajaran - Sumakul, Hansen Imanuel; Tendean, Selina Valensia; Lonto, Apeles Lexi (Tumoutou Social Science Journal, 2024)
Advances in Information Technology have encouraged many changes, including in the field of education which gave birth to the concept of e-learning. With e-learning, implementation of learning becomes more effective and efficient. E-learning allows participants educate to be active and creative. E-learning provides students, educators, and managers education can benefit from many benefits, among them the flexibility of programs and materials Learning can be made more interesting and memorable. Integration of information technology on education will improve the quality of learning. Impacts associated with integration Information technology in education is encouraging the acceleration of computer literacy in Indonesian society. Utilization of technology as a learning medium in the learning process teaching, can make it easier for teachers to communicate and interact with students both in the classroom and outside the classroom. The need for technology in the realm education is nothing new, the use of technology to form learners conducive and innovative. This utilization has proven to play a major role in the smooth running of the process Study.